If the natural number X is a multiple of 3, the summary of each digit number of X is a multiple of 3 too.
Example:
3 = 3 * 1; For single digit, it's ovbious that the result is multiple of 3. 6 = 3 * 2; ... 12 = 3 * 4; (1 + 2) = 3 = 3 * 1 15 = 3 * 5; (1 + 5) = 6 = 3 * 2 18 = 3 * 6; (1 + 8) = 9 = 3 * 3 21 = 3 * 7; (2 + 1) = 3 = 3 * 1 24 = 3 * 8; (2 + 4) = 6 = 3 * 2 27 = 3 * 9; (2 + 7) = 9 = 3 * 3 30 = 3 * 10; (3 + 0) = 3 = 3 * 1 33 = 3 * 11; (3 + 3) = 6 = 3 * 2 36 = 3 * 12; (3 + 6) = 9 = 3 * 3 ... 99 = 3 * 33; (9 + 9) = 18 = 3 * 6 ... 2274 = 3 * 758; (2 + 2 + 7 + 4) = 15 = 3 * 5 ...
Let's say the natural number X is 2 digits.
X can be expressed as the following using natural number a and b.
In this case, a summary of each digit is a + b
.
X = a + b * 10
And the number X can be written as following using another natural number Y.
X = 3 * Y
Conbining the 2 equisitions.
a + b * 10 = 3 * Y a + b * (1 + 9) = 3 * Y a + b * 1 + b * 9 = 3 * Y ~~~~~ move to right side a + b = 3 * Y - b * 9 ~~~~~~~ = 3 * Y - b * 3 * 3 ~~~ ~~~ = 3 * (Y - b * 3)
i.e., If the number X is a multiple of 3, the sum of each digit number (a + b) is multiple of 3.
Let's move to multiple digits of X.
Let's say there is a number X which is multiple digits and is a multiple of 3.
The number X can be expressed as the following equation.
In this case the summary of each digit of X is a + b + c + d + ...
.
X = a + b * 10 + c * 100 + d * 1000 + ... ~~~~~~ ~~~~~~~ ~~~~~~~~ = a + b * (1 + 9) + c * (1 + 99) + d * (1 + 999) + ... ~~~~~~~~~~~ ~~~~~~~~~~~~ ~~~~~~~~~~~~~ ~~~ = a + b + c + d + ... + b * 9 + c * 99 + d * 999 + ... ~~~~~~~~~~~~~~~ ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ = a + b + c + d + ... + b * 9 + c * 9 * 11 + d * 9 * 111 + ... ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ = a + b + c + d + ... + 9 * (b + c * 11 + d * 111 + ...) ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
By the way, the number X is a multiple of 3, X can be expressed as the following equation with an integer Y.
X = 3 * Y
The above 2 equations are identical.
a + b + c + d + ... + 9 * (b + c * 11 + d * 111 + ...) = 3 * Y
Transforming the above equation to leave a summary of each digit left side, the right side of the equation is a multiple of 3.
a + b + c + d + ... + 9 * (b + c * 11 + d * 111 + ...) = 3 * Y ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ move to right side a + b + c + d + ... = 3 * Y - 9 * (b + c * 11 + d * 111 + ...) ~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~ = 3 * Y - 3 * 3 * (b + c * 11 + d * 111 + ...) ~~~ ~~~ = 3 * (Y - 3 * (b + c * 11 + d * 111 + ...)) ~~~
i.e., If the number X is multiple of 3, a summary of each digit of X is multiple of 3.